Albian gastropods of the rudist-bearing Mal Paso Formation, Chumbitaro region, Guerrero, Mexico - Blanca Estela Buitrón; Jerjes Pantoja-Alor (Revista Mexicana de Ciencias Geológicas)
The Mal Paso Formation (Albian) consists of more than 750 m of highly fossiliferous sedimentary rocks exposed in the Chumbítaro region, State of Guerrero. The Mal Paso Formation is divided into two members: a lower clastic member that records continental-marine deltaic environment… in order to continue, download the full paper in PDF.